Theological Values Internalization in Central Learning Management at Kindergarten - Tutuk Ningsih; Novan Ardy Wiyani (Edukasia Islamika, 2021)
Parents are more aware of the urgency of spiritual intelligence for their children. Spiritual intelligence is the ability of a person to always present his Lord in every activity. Various studies show that one of the success factors people is mostly determined by his spiritual intelligence. Parents also want the teacher to be able to develop their children's spiritual intelligence. This desire was responded to by the head of kindergarten al-Irsyad al-Islamiyyah Purwokerto by managing the learning central based on theological values. This qualitative research is intended to describe the internalization of theological values in the management of learning centrals in kindergarten al-Irsyad al-Islamiyyah Purwokerto. Data were collected using interview, observation, and documentation techniques and then analyzed using the Miles and Huberman data analysis technique. The results showed that the internalization of theological values in the management of learning centrals was carried out through five attempts. First, the internalization of theological value into the vision and quality assurance of graduates. Second, the internalization of theological values by organizing ritual centrals. Third, the internalization of theological values by integrating religion and science into learning themes. Fourth, the internalization of theological values through habituation activities. Fifth, the internalization of theological value through the activities of telling stories about the Prophet and the Prophet and the Companions of the Prophet. The implication of internalization theological values in the management of learning centrals is that students become obedient individuals to their Lord, their Prophet, and their teachers and parents.